Preparations for the nixon round - Peter Hermes (Intereconomics, 1973)
The next round of GATT negotiations—the so-called “Nixon Round”—will be opened at the ministerial level in Tokyo on September 12–14, 1973, and probably continue for several years in Geneva. Less developed countries (LDCs) which have not joined GATT but nevertheless wish to participate in the negotiations are to be invited for the first time. UNCTAD and IMF will be among the most directly engaged observers.
Keywords: 330; Foreign Trade